2016
DOI: 10.1515/hepo-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Tribulus terrestris methanol extract against clinical isolates of Escherichia coli

Abstract: S u m m a r yIntroduction: Tribulus terrestris L. is traditionally used for treatment of urinary tract infections. Escherichia coli, as the most prominent agent of urinary tract infections, can be sensitive to T. terrestris extract. Objectives: The aim of this study was to evaluate the antibacterial activity of T. terrestris methanol extract against clinical isolates of E. coli from urinary tract infections. Saponins were determined as main constituents of T. terrestris methanol extract. Methods: The antibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…The same study reported that the complex extract of T. terrestris, Capsella bursa-pastoris, and Glycyrrhiza glabra exhibited superior and synergistic effects compared to individual extracts. Various other studies revealed antibacterial activity of T. terrestris extracts against a number of Gram-positive and Gram-negative bacterial strains [ 51 – 54 ]. All previous studies and our findings proved the antimicrobials efficacy of T. terrestris .…”
Section: Resultsmentioning
confidence: 99%
“…The same study reported that the complex extract of T. terrestris, Capsella bursa-pastoris, and Glycyrrhiza glabra exhibited superior and synergistic effects compared to individual extracts. Various other studies revealed antibacterial activity of T. terrestris extracts against a number of Gram-positive and Gram-negative bacterial strains [ 51 – 54 ]. All previous studies and our findings proved the antimicrobials efficacy of T. terrestris .…”
Section: Resultsmentioning
confidence: 99%
“…This plant has shown several pharmacological activities including antioxidant, cardiotonic, antimicrobial, antihypertensive, anticancer, and analgesic characteristics [ 92 , 93 ]. The Iranian and Turkish tribulus has been shown to have high antibacterial activity [ 94 , 95 ]. The antimicrobial activity of different extracts from tribulus was examined against eleven microorganisms including E. coli , S. aureus , Bacillus cereus , Corynebacterium diphtheria , Salmonella typhimurium , Candida albicans , Proteus vulgaris , K. pneumonia (Klebsiella pneumonia) , S. marcescens (Serratia marcescens) , and Pseudomonas aeruginosa .…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…There are several in vitro studies that have revealed the antibacterial potency of TT total or fractionated extracts on Gram-negative and Gram-positive bacterial strains. Among the Gram-positive bacteria, facultative anaerobe strains such as Staphylococcus aureus, Streptoccocus mutans, Streptococcus sanguinis, Actinomyces viscosus, Enteroccocus faecalis, and Bacillus subtilis were susceptible and among the Gram-negative bacteria Escherichia coli, Salmonella typhi, Proteus mirabilis, and Klebsiella pneumoniae were susceptible [87][88][89][90][91][92]. It is still unclear which components are responsible for the antibacterial activity, but alkaloids contribute to the general antibacterial effect of the total extracts [88].…”
Section: Antibacterial Activitymentioning
confidence: 99%